The Effect of Leadership Style and Work Discipline on Employee Performance at the Sultan Bantilan Class III Meteorological Station Office, Tolitoli Regency Central Sulawesi Province - Idris Simon; Farid; Henni Mande (Jurnal Sinar Manajemen, 2024)
This study aims to analyze the influence of leadership style and work discipline on employee performance at the Sultan Bantilan Class III Meteorological Station Office, Tolitoli Regency, Central Sulawesi Province. With quantitative research methods, data is collected through questionnaires distributed to employees. The results of the analysis showed that there was a significant positive influence between leadership style and work discipline on employee performance. An effective leadership style is able to motivate employees, while high work discipline contributes to improved work performance. This research makes an important contribution to human resource management in government agencies, with recommendations to increase employee motivation and discipline to achieve optimal performance.